Five charters concerning the early history of the chapter at Avranches - Allen, R (OpenEdition, 2008)
The cartulary of Avranches cathedral, known as the Livre vert, contains five important charters concerning the deanship of Avranches. Known to nineteenth-century antiquarians, but overlooked by modern scholarship, the charters have never been studied despite their significance for the early history of the Avranches chapter. The following article not only discusses the creation of the deanship, an event that saw the completion of a process of renewal that had begun in the diocese at the end of the tenth-century, but also provides critical editions of all five acts. These include hitherto unpublished charters of Hugh of Amiens, archbishop of Rouen.